FIGURATIVE LANGUAGE IN KAKONG COMMUNITY: A Study in Lombok Island - Nurun Hidayati (Journal of English Education, 2017)
The current research aims to find the types and functions of figurative languages commonly used by Kakong Community. The data gathered through observation, note taking, and interview then analyzed through the interactive model. At the end, the study concluded that: 1). the types of figurative languages that commonly used by Kakong community are similes, metaphors, and idioms. 2). the functions of those figurative languages are to maintain social relation, to criticize, to insult, and to give comment about something. 3). Using figurative language is preferable for Kakong community. The study also recommending that: 1). Kakong community has the obligation to save their language. 2). Preserving figurative language as one of the old culture heritages needs to be considered by extending further research. 3). People of Kakong community should be proud of having figurative language and they are supposed to use them continually. 4). the hidden values in figurative language need to be understood to get a better relationship in social life.